Peran dan Gaya Kepemimpinan Sekretaris Dewan Dalam meningkatkan Kompetensi Pegawai Pada Sekretariat DPRD Kabupaten Badung - I Made Galih Kayana Suwikantara; I Ketut Winaya (UIR Press, 2023)
The Secretariat of the Regional Representatives Council of Badung Regency or known as Badung Regency Secretariat is an institution within the Badung Regency administration which has the duties and functions of providing administrative services and assisting the DPRD in helping out its functions and duties. The purpose of this study is to find out how the role and leadership style of the board secretary in improving the competence of employees at the Badung Regency DPRD Secretariat. This study uses a qualitative descriptive method with data collection techniques, namely interviews, observation, and documentation. Based on the data collection methods and techniques used, the authors obtained data that the role of the Board Secretary as a leader, Liason Manager, and figurehead has been going well. This can be seen from the leadership style used by the Board Secretary, namely an employee-oriented leadership style, where through and focus on how to motivate employees rather than control them. Through the leadership style of the Board Secretary, there are several ways to improve the competence of employees. Among them is by providing good training through seminars, training, mentoring, and working visits outside the region so that employees can increase competence both theoretically and creatively in developing innovations at work.